Teaching-learning Physics in Bilingual Education Schools for the Deaf - Ellen Cristine Prestes Vivian; André Ary Leonel (Revista Brasileira de Pesquisa em Educação em Ciências, 2022)
With the objective of investigating the challenges and contributions presented about the physics teaching-learning process in bilingual schools and special education schools for the deaf, a bibliographic review was conducted in the annals of three of the biggest national events that cover physics teaching: the National Symposium on Physics Education (SNEF), the National Meeting of Research in Science Education (ENPEC), and the Meeting on Research in Physics Teaching (EPEF). This was a qualitative study that employed content analysis to analyze the data. Only five articles were found to bring teaching-learning aspects within this context. These five articles were discussed within two emerging categories: (i) the challenges and difficulties in teaching-learning physics in a bilingual school; (ii) the actions and contributions to the teaching-learning of physics in the bilingual school. Recognizing Brazilian Sign Language (Libras) alongside bilingualism pushes the inclusion and teaching-learning process for the deaf to their full potential. In order to overcome some obstacles, including difficulties related to deaf students’ literacy of the written language or educators’ lack of familiarity with signs specific to physics, more significant investments are needed in the production of bilingual material, in addition to creating and spreading signs and educators’ familiarity with deaf culture.